Black-blood multicontrast imaging of carotid arteries with DANTE-prepared 2D and 3D MR imaging. - Li, L; Chai, J; Biasiolli, L; Robson, M; Choudhury, R; Handa, A; Near, J; Jezzard, P (Radiological Society of North America Inc., 2014)
PURPOSE: To prospectively compare the black-blood ( BB black blood ) imaging efficiency of a delay alternating with nutation for tailored excitation ( DANTE delay alternating with nutation for tailored excitation ) preparation module with conventional double inversion-recovery ( DIR double inversion recovery ) and motion-sensitive driven equilibrium ( MSDE motion-sensitive driven equilibrium ) preparation modules and to introduce a new three-dimensional ( 3D three-dimensional ) T1-weighted magnetic resonance (MR) imaging sequence. MATERIALS AND METHODS: Carotid artery wall imaging was performed in 10 healthy volunteers and 15 patients in accordance with an institutional review board-approved protocol. Two-dimensional ( 2D two-dimensional ) turbo spin-echo ( TSE turbo spin echo ) and 3D three-dimensional fast low-angle shot ( FLASH fast low-angle shot ) sequences served as readout modules. DANTE delay alternating with nutation for tailored excitation -prepared T1-, T2-, and proton density-weighted 2D two-dimensional TSE turbo spin echo images, as well as T1-weighted 3D three-dimensional DANTE delay alternating with nutation for tailored excitation -prepared FLASH fast low-angle shot (hereafter, 3D three-dimensional DASH DANTE-prepared FLASH ) images, were acquired in the region of the carotid artery bifurcation. For comparison, 2D two-dimensional DIR double inversion recovery -prepared, 2D two-dimensional MSDE motion-sensitive driven equilibrium -prepared multicontrast TSE turbo spin echo , and 3D three-dimensional MSDE motion-sensitive driven equilibrium -prepared FLASH fast low-angle shot (hereafter, 3D three-dimensional MERGE MSDE-prepared FLASH ) MR images were also acquired. The effective contrast-to-noise ratio ( CNReff effective contrast-to-noise ratio ) per unit time was calculated for all sequences. Paired t tests were performed to test within-group differences in vessel wall CNReff effective contrast-to-noise ratio . RESULTS: The CNReff effective contrast-to-noise ratio of DANTE delay alternating with nutation for tailored excitation -prepared T1-, T2-, and proton density-weighted sequences was 27.3, 14.7, and 25.7 mm(-1)min(-1/2), respectively; this represented an improvement of approximately 25%-100% (P < .05) when compared with the CNReff effective contrast-to-noise ratio attained with existing methods. The 3D three-dimensional DASH DANTE-prepared FLASH technique proved to be a fast (<2 seconds per section) and high-spatial-resolution (0.6 mm isotropic) BB black blood technique with higher (75%-100% improvement, P < .001) signal-to-noise ratio efficiency than the 3D three-dimensional MERGE MSDE-prepared FLASH technique. CONCLUSION: The DANTE delay alternating with nutation for tailored excitation -prepared multicontrast 2D two-dimensional BB black blood technique is a promising new tool for MR imaging of carotid artery walls. Additionally, the 3D three-dimensional DASH DANTE-prepared FLASH sequence enables 3D three-dimensional high-spatial-resolution fast T1-weighted imaging of carotid artery walls. ©RSNA, 2014 Online supplemental material is available for this article .